Analisis Kandungan Tanah Pada Media Pertumbuhan Tanaman Pacar Air (Impatiens balsamina) Di Kabupaten Jombang - Dyah Ayu Sri Hartanti; Awang Nia Agustin (FMIPA : Universitas PGRI Adi Buana, 2021)
This research was conducted to determine the soil content in the growth media of water pacar air plants (Impatiens balsamina) in Jombang Regency. This study uses qualitative methods. Random soil sampling is performed by determining the soil sampling points randomly, but spreads evenly throughout the represented area of the soil. Soil content analysis is done using several methods namely Kjeldahl method for nitrogen analysis, Olsen method for phosphorus analysis and, Walkley and Black method for C-organic analysis. The results showed the status of soil content in the research area is classified as low to very high parameters or has not met soil fertility standards. In Nglajur Village, Peterongan subdistrict has dark grayish brown soil color, sandy clay texture and Trawasan Subdistrict Village has dark gray soil color textured dusty clay. Keywords: Pacar Air Plants, Soil, Nutrients, Soil Fertility